2014
DOI: 10.4103/2156-7514.139735
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Findings in a Large Series of Patients with Knee Pain

Abstract: Background:Musculoskeletal ultrasound (MSKUS) is becoming more and more popular in the evaluation of different musculoskeletal abnormalities. The aim of this retrospective study was to document the prevalence and spectrum of MSKUS findings at the painful knee.Materials and Methods:All the studies of MSKUS that were performed for the evaluation of knee pain during the previous 2 years at the Department of Radiology in Nazareth hospital were reviewed. Demographic and clinical parameters including age, gender, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…Ultrasound is becoming more popular in the evaluation of different musculoskeletal abnormalities such as different rheumatic disease, soft tissue lesions, and joints [10][11][12][13][14]. Few studies discuss the role of ultrasound in knee joint [15][16][17] as well as ultrasound findings in patients with knee osteoarthritis [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound is becoming more popular in the evaluation of different musculoskeletal abnormalities such as different rheumatic disease, soft tissue lesions, and joints [10][11][12][13][14]. Few studies discuss the role of ultrasound in knee joint [15][16][17] as well as ultrasound findings in patients with knee osteoarthritis [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are significant limitations of using MRI, such as the presence of indwelling cardiac pacemakers, metal implants, patient intolerance due to claustrophobia and delay in treatment due to long wait periods [ 1 2 3 ]. As a result, recent studies have demonstrated point-of-care ultrasound (POCUS) as an alternative, non-invasive and real-time imaging modality to evaluate the soft tissue pathology of the knee, including injuries to the medial meniscus and medial collateral ligament (MCL) [ 3 4 5 6 7 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cross-sectional studies the Newcastle-Ottava quality scores ranged from 2 to 9 stars with a median score of 5.5 (maximum 10). Three studies scored less than five 28 , 36 , 37 . In general, all samples were selected non-randomly, provided adequate definition of cases (ACR-criteria for OA diagnosis or validated tool for knee pain assessment) and blinded US assessment.…”
Section: Resultsmentioning
confidence: 99%